2006
DOI: 10.1016/j.virol.2006.01.042
|View full text |Cite
|
Sign up to set email alerts
|

The expression of p16INK4a tumor suppressor is upregulated by human cytomegalovirus infection and required for optimal viral replication

Abstract: The human cytomegalovirus (HCMV) induces a replicative senescence program after arresting host cell cycle progression so as to create a favorable environment for its replication. Here, we report that HCMV infection stimulates the expression of p16(INK4a), a direct effector of the senescence phenotype. The increase in p16(INK4a) gene expression was due to an increase in gene transcription, since the expression of a reporter gene driven by the p16(INK4a)-encoding CDKN2A gene promoter was strongly induced by HCMV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…We were particularly interested in events occurring at times prior to the failure of the pUL117-deficient virus to block host DNA synthesis (i.e., 0–36 hpi) as misregulation of these events was the most likely cause of the defect. HCMV up-regulates p16 at late times [13],[30], inhibits cyclin A accumulation [8],[31],[32], and prevents MCM complex loading onto chromatin [17],[18]. When infecting G0-synchronized HFFs in the presence of serum, HCMV induced p16 accumulation and expressed another viral inhibitory protein IE2 independent of pUL117 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We were particularly interested in events occurring at times prior to the failure of the pUL117-deficient virus to block host DNA synthesis (i.e., 0–36 hpi) as misregulation of these events was the most likely cause of the defect. HCMV up-regulates p16 at late times [13],[30], inhibits cyclin A accumulation [8],[31],[32], and prevents MCM complex loading onto chromatin [17],[18]. When infecting G0-synchronized HFFs in the presence of serum, HCMV induced p16 accumulation and expressed another viral inhibitory protein IE2 independent of pUL117 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although telomere shortening has been shown in acute infections in experimental animal models (Asghar, Hasselquist, et al., 2015; Asghar et al., 2016; Ilmonen et al., 2008), such effect has not been reported in humans. Previous studies have shown that chronic viral infections (i.e., HCV, CMV, and HIV) accelerate cellular aging in humans, as reflected by shorter telomere length and elevated CDKN2A expression (van de Berg et al., 2010; Gianesin et al., 2016; Leung et al., 2017; Pathai et al., 2013; Robinson et al., 2013; Zannetti et al., 2006). Furthermore, genome‐wide association studies (GWAS) have linked CDKN2A to many age‐related pathologies, including susceptibility to frailty and increased risk of coronary artery disease, myocardial infarction, type 2 diabetes, and Alzheimer's disease (Jeck et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In this study of acute malaria infection, we find distinct dynamics of cellular aging not observed during chronic infection (van de Berg et al., 2010; Gianesin et al., 2016; Leung et al., 2017; Pathai et al., 2013; Robinson et al., 2013; Zannetti et al., 2006). After successful treatment and in the absence of new infections, the effect on cellular aging markers was largely reversed as reflected by lower CDKN2A expression, higher telomerase activity, and gradual restoration of telomere length in peripheral blood of travelers from three months postinfection up to one year.…”
Section: Discussionmentioning
confidence: 99%
“…31 Highly purified HCMV stocks propagated in low-passage human embryonic lung (HEL) fibroblasts were used. 32 Lowpassage HEL cells and the laboratory type strain AD169 from American Type Culture Collection (VR-538; ATCC, Manassas, VA) were propagated at low virus-to-cell ratios (about 0.001 plaque-forming units [PFUs]/cells) to minimize generation of defective particles. Infections were initiated by intraperitoneal injection of 10 5 (BALB/c), 5 ϫ 10 5 (C57BL6, PTX3 ϩ/ϩ , and PTX3 Ϫ/Ϫ ) PFUs of MCMV.…”
Section: Pathogens Infections and Treatmentsmentioning
confidence: 99%
“…Cycling conditions were initial denaturation for 3 minutes at 95°C, followed by cycles of 1 minute at 95°C, 1 minute at 50°C, and 20 seconds at 72°C, and a final extension for 10 minutes at 72°C. To determine HCMV DNA copy number, total DNA was isolated as described 32 and viral DNA levels were measured by real-time RT-PCR using the Q-CMV Real Time Complete Kit (Nanogen Advanced Diagnostics, Turin, Italy), which amplifies the major immediate early antigen, HCMVUL123. The RT-PCR products were detected by measuring fluorescence with passive reference dye in Sequence Detection System ABI Prism 7300 (Applied Biosystems-Applera Italia-Monza, Milan, Italy).…”
Section: Quantification Of CMV Mrna and Dnamentioning
confidence: 99%